EFORT recommendations for off-label use, mix & match and mismatch in hip and knee arthroplasty. Issue 11 (November 2021) - Tucker, Keith; Günther, Klaus-Peter; Kjaersgaard-Andersen, Per; Lützner, Jörg; Kretzer, Jan Philippe; Nelissen, Rob G.H.H.; Lange, Toni; Zagra, Luigi
Abstract : Off-label use is frequently practiced in primary and revision arthroplasty, as there may be indications for the application of implants for purposes outside the one the manufacturers intended. Under certain circumstances, patients may benefit from selective application of mix & match. This can refer to primary hip arthroplasty (if evidence suggests that the combination of devices from different manufacturers has superior results) and revision hip or knee arthroplasty (when the exchange of one component only is necessary and the invasiveness of surgery can be reduced). Within the EFORT 'Implant and Patient Safety Initiative', evidence- and consensus-based recommendations have been developed for the safe application of off-label use and mix & match in primary as well as revision hip and knee arthroplasty. Prior to the application of a medical device for hip or knee arthroplasty off-label and within a mix & match situation, surgeons should balance the risks and benefits to the patient, obtain informed consent, and document the decision process appropriately. Nevertheless, it is crucial for surgeons to only combine implants that are compatible. Mismatch of components, where their sizes or connections do not fit, may have catastrophic effects and is a surgical mistake. Surgeons must be fully aware of the features of the components that they use in off-label indications or during mix & match applications, must be appropriately trained and must audit their results. Considering the frequent practice of off-label and mix & match as well as the potential medico-legal issues, further research is necessary to obtain more data about the appropriate indications and outcomes for those procedures. Cite this article: EFORT Open Rev 2021;6:982-1005. DOI: 10.1302/2058-5241.6.210080